Bibliometric Analysis of Nasopharyngeal Carcinoma Based on CiteSpace - CHEN Dayang; ZONG Zengyan; XIONG Dan; WANG Mengmeng; DOU Xiaowen; JI Xiang; ZHANG Xiuming (Zhongliu Fangzhi Yanjiu, 2020)
Objective To analyze the research status and development trend of nasopharyngeal carcinoma, to provide a reference for the research of nasopharyngeal cavcinoma in China. Methods We retrieved research articles about nasopharyngeal carcinoma from 2009 to 2019 in the Web of Science (WOS) core database of USA. The number of published articles, research institutions, citations and keywords of the literature were analyzed through the statistical tools provided by CiteSpace and WOS database, and the word frequency, centrality and clustering status of keywords were explored. Results After screening, a total of 4841 articles were obtained, and the number of published articles increased year by year. The top 10 keywords with the highest frequency and top 10 keywords with the highest centrality mainly focus on the treatment and pathogenesis of nasopharyngeal carcinoma. The clustering results concentrated on poor prognosis, advanced nasopharyngeal carcinoma, clinical target area mapping and isopentenyl isoflavones. Conclusion The research hotspot of nasopharyngeal carcinoma is closely related to the geographical distribution of patients. The current research focuses on the treatment and pathogenesis of nasopharyngeal carcinoma.